Plasma D-Dimer as a Marker for Postoperative Deep Venous Thrombosis - Dunn, Irene D; Hui, Anthony C W; Triffitt, Paul D; Crozier, Ann E C; Gregg, Paul J; Sinclair, Marie E; Lynn Armstrong, A; Mitchell, Vivian E (Thrombosis and Haemostasis, 1994)
Plasma levels of D-dimer have been found useful as a marker of deep venous thrombosis in those patients in whom thrombosis is suspected, but their usefulness in postoperative screening is less clear. We have investigated the relationship of D-dimer to deep venous thrombosis in 90 patients after total hip and knee arthroplasty. From the first postoperative day the D-dimer levels were found to be highly significantly raised in patients with deep venous thrombosis. A combined result over the first six postoperative days in excess of 1200ng/ml correlated with thrombosis with a specificity of 100%, sensitivity of 45%, positive predictive value of 60%, and negative predictive value of 100%. However, individual estimations were not discriminatory.